Zinc Oxide Nanoparticles Improve Pleioblastus pygmaeus Plant Tolerance to Arsenic and Mercury by Stimulating Antioxidant Defense and Reducing the Metal Accumulation and Translocation - Emamverdian, Abolghassem; Hasanuzzaman, Mirza; Ding, Yulong; Barker, James; Mokhberdoran, Farzad; Liu, Guohua (Frontiers in Plant Science, 2022)
The utilization of nanoparticles to potentially reduce toxicity from metals/metalloids in plants has increased in recent years, which can help them to achieve tolerance under the stressful conditions. An in vitro experiment was conducted to investigate five different levels of zinc oxide nanoparticles (ZnO-NPs) (0, 50, 100, 150, and 200 µM) both alone and in combination with 150 µM arsenic (As) and 150 µM mercury (Hg) in one-year-old Pleioblastus pygmaeus(Miq.)Nakai plants through four replications. The results demonstrated that As and Hg alone had damaging effects on the plant growth and development. However, the addition of various concentrations of ZnO-NPs led to increased antioxidant and nonantioxidant enzyme activity, proline (Pro;79%) content, glycine betaine (GB;71%) content, tyrosine ammonia-lyase (TAL;43%) activity, phenylalanine ammonia-lyase (PAL;69%) activity, chlorophyll indices, and eventually plant biomass, while the lipoxygenase activity (LOX), electrolyte leakage (EL), soluble protein (SP), hydrogen peroxide (H2O2) content, and thiobarbituric acid reactive substances (TBARS) were reduced. We concluded that ZnO-NPs detoxified As and Hg toxicity in the plants through increasing antioxidant activity, reducing As and Hg accumulation, As and Hg translocation from roots to shoots, and adjusting stomatal closure. This detoxification was further confirmed by the reduction of the translocation factor (TF) of As and Hg and the enhancement of the tolerance index (TI) in combination with ZnO-NPs. However, there is a need for further investigation with different metals/metalloids.